2023
DOI: 10.1039/d3gc00011g
|View full text |Cite
|
Sign up to set email alerts
|

Accessing secondary amine containing fine chemicals and polymers with an earth-abundant hydroaminoalkylation catalyst

Abstract: Titanium-catalyzed hydroaminoalkylation has emerged as an atom-economical, earth-abundant synthesis of N-containing products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…These Dq values are intermediate between those observed for [CrCl 6 ] 3− (1360) and [Cr(en) 3 ] 3+ (2188) 75,76 as might be expected. The absorption peak B (Figure 4) in the region 439−468 nm can be attributed to 4 A 2g → 4 T 1g (F) v 2 transition. 77,78 The spacing between the v 1 and v 2 transitions of the neutral complexes (4485 cm −1 for 3 and 4303 cm −1 for 4) is smaller than that for the cationic complexes (5656 cm −1 for 1 and 5926 cm −1 for 2).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These Dq values are intermediate between those observed for [CrCl 6 ] 3− (1360) and [Cr(en) 3 ] 3+ (2188) 75,76 as might be expected. The absorption peak B (Figure 4) in the region 439−468 nm can be attributed to 4 A 2g → 4 T 1g (F) v 2 transition. 77,78 The spacing between the v 1 and v 2 transitions of the neutral complexes (4485 cm −1 for 3 and 4303 cm −1 for 4) is smaller than that for the cationic complexes (5656 cm −1 for 1 and 5926 cm −1 for 2).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…72 A considerable redshift and broadening were observed in the peak absorption wavelength on going from the cationic complexes 1 and 2 to the neutral complexes 3 and 4. The order of the spin-allowed ligand field transitions characteristic of a Cr(III) complex with d 3 electronic configurations is 4 73,74 We use these octahedral field symmetry labels in our work for comparison with assignments for literature complexes, even though our complexes are distorted from this ideal geometry. The low energy transition B in the region of 578−586 nm, the 4 A 2g → 4 T 2g (v 1 ), has the energy of the ligand field splitting 10Dq (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The LCA methodology has been utilized for similar studies evaluating the potential environmental impacts associated with industrial chemical production and comparing the different production approaches based on their level of impacts. Mostly all the sectors are covered: fossil-based industry, , biobased fuels and chemicals, pharmaceuticals, and the synthesis of new catalytic system from earth-abundant metals. Studies presented above, along with several others, established the suitability of the LCA methodology for pinpointing areas where different approaches to the production of chemical compounds excel in terms of environmental performance and the possible areas where process improvement efforts should be concentrated to drive significant environmental gains.…”
Section: Methodsmentioning
confidence: 99%
“…Amine-functionalized polyolefins can be made by the reduction of nitrile butadiene rubber or by protocols featuring hydro­formylation (Scheme A), , hydro­boration, or hydro­halogenation, followed by reaction with an amine. We have shown that hydro­amino­alkylation with N , O -chelated tantalum or titanium catalysts is a powerful postpolymerization amination strategy to make amine-terminated polypropylene (Scheme B). , Here, we report hydro­aminoalkylation for the postpol­ymerization modification of commercially available liquid PBD to access a new class of polyolefins with tunable amounts of amine functionalization to target desired physical properties (Scheme C).…”
mentioning
confidence: 98%
“…We have shown that hydroaminoalkylation with N,O-chelated tantalum or titanium catalysts is a powerful postpolymerization amination strategy to make amineterminated polypropylene (Scheme 1B). 49,50 Here, we report hydroaminoalkylation for the postpolymerization modification of commercially available liquid PBD to access a new class of polyolefins with tunable amounts of amine functionalization to target desired physical properties (Scheme 1C). Initial reaction screening was performed on a small scale with the 28 wt% 1,2-PBD, PBD13 51 (2500 g/mol M n , 13 vinyl groups/chain on average), and 13.0 equiv of N-methylaniline (HNMePh).…”
mentioning
confidence: 99%